Effects of exogenous nitric oxide on the growth and quality of Leonurus japonicus under drought stress - LU Xing; YAO Wenrong; GENG Zhuoqing; SHANG Shuqi; ZHANG Yihua (Xibei zhiwu xuebao)
[Objective] This study aims to explore the regulation of exogenous nitric oxide (NO) on the growth and quality of Leonurus japonicus under drought stress, in order to provide theoretical basis for cultivation and quality improvement of L. japonicus under drought stress. [Methods] 100 μmol/L sodium nitroprusside (SNP, a NO donor) was used as pretreatment, and 10%, 20%, and 30% polyethylene glycol (PEG)-6000 was used to simulate different degrees of drought stress. The effect of exogenous NO on seed germination, seedling growth, and the content of medicinal components of L. japonicus seedlings under drought stress was analyzed. [Results] (1) Seed germination under 10% and 20% PEG treatment was improved by the regulation of amylase activity through exogenous NO. (2) Exogenous NO mitigated growth inhibition of L. japonicus seedlings under drought stress, which was likely attributable to the reduction in malondialdehyde and hydrogen peroxide levels, thereby decreasing oxidative damage. (3) Analysis of medicinal components showed that exogenous NO enhanced leonurine hydrochloride content, stachydrine hydrochloride content, and flavonoid biosynthesis in L. japonicus under drought stress. [Conclusion] Exogenous application of NO could alleviate seed germination and seedling growth of L. japonicus under mild and moderate drought stress, and promote the accumulation of medicinal components under stress.